Heritage Authenticity as a Source of Personal and Collective Identity - Pirkovič, Jelka (Protection of Cultural Heritage, 2025)
The pursuit of authenticity has been driving heritage discourse, stemming from the early efforts of heritage theory. My contribution provides a comprehensive view of heritage authenticity from an existential standpoint. I draw upon Martin Heidegger's Dwelling, Building and Thinking, which offers contrasting perspectives on human existence within time and place: caring and cultivating versus creating and destroying. From this contrast, it becomes evident that heritage embodies authenticity when it reinforces caring and cultivating shared values. With this, authentic caring allows heritage to endure and contributes to constructive development and adaptive changes while respecting the spirit of place. Viewing heritage authenticity through psychological and philosophical lenses emphasises its significance in personal and collective identity formation. Understanding “the other” is essential in shaping our identities. This paradox is also evident in heritage and can be addressed by fostering a more inclusive approach that embraces and integrates the heritage of others. Such an approach challenges the conventional understanding of the interplay between heritage authenticity and identity. Authenticity and identity depend on heritage values, memories, and knowledge. Through this relationship, a society becomes visible to itself and others. Building on Martin Heidegger and Alessandro Ferrara’s understanding, the authentic identity expressed in heritage provides valuable insights into a society's identification process.